A scalable multiagent architecture for monitoring IoT devices. (1st August 2019) - Rocha, Vladimir; Brandão, Anarosa Alves Franco
Abstract: In recent years, the use of wireless devices has experienced huge grown, mainly due to the decrease in cost, size and energy consumption. Research in the Internet of Things have concentrated their efforts on how to monitor these devices taking into account both scalability and efficiency while searching and updating continuously device information. In order to do that, current alternatives combine a widely recognized method, the data aggregation, and a widely adopted distributed structure, called Distributed Hash Table, which form groups of devices, saving energy by minimizing the number of transmissions. However, scalability is still a key challenge when the group comprises a large number of devices. In this paper, we propose a scalable architecture that creates agents to distribute the responsibility of managing groups and the interaction among them, such as merging and splitting, and shares the data aggregation with the devices of group frontier. Experimental results showed the viability of adopting this architecture if compared to the most widely used current approaches.